Robust two-dimensional topological insulators in methyl-functionalized bismuth, antimony, and lead bilayer films - Ma, Yandong; Dai, Ying; Kou, Liangzhi; Frauenheim, Thomas; Heine, Thomas (Nano Letters, 2015)
One of the major obstacles to a wide application range of the quantum spin Hall (QSH) effect is the lack of suitable QSH insulators with a large bulk gap. By means of first-principles calculations including relativistic effects, we predict that methyl-functionalized bismuth, antimony, and lead bilayers (Me-Bi, Me-Sb, and Me-Pb) are 2D topological insulators (TIs) with protected Dirac type topological helical edge states, and thus suitable QSH systems. In addition to the explicitly obtained topological edge states, the nontrivial topological characteristic of these systems is confirmed by the calculated nontrivial Z2 topological invariant. The TI characteristics are intrinsic to the studied materials and are not subject to lateral quantum confinement at edges, as confirmed by explicit simulation of the corresponding nanoribbons. It is worthwhile to point out that the large nontrivial bulk gaps of 0.934 eV (Me-Bi), 0.386 eV (Me-Sb), and 0.964 eV (Me-Pb) are derived from the strong spin-orbit coupling within the px and py orbitals and would be large enough for room-temperature application. Moreover, we show that the topological properties in these three systems are robust against mechanical deformation. These novel 2D TIs with such giant topological energy gaps are promising platforms for topological phenomena and possible applications at high temperature.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Dirac states; Large band gap; Quantum spin Hall effect; Strain engineering; Topological insulators; Two-dimensional material